Biomass and Nutrient Accumulation by Dual-Purpose Hemp and Concurrent Soil Profile Water Depletion at Three Locations in Kansas in 2022 - Kraig Roozeboom; Jason Griffin; Scott Dooley; Gerard Kluitenberg; Dorivar Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2023)
Hemp has garnered interest as a potential crop that is not constrained by the typical food, feed, and fuel market channels. Although hemp varieties are available for either grain, fiber, or both (dual-purpose: both grain and fiber) markets, little information is available on hemp growth and water use in Kansas environments. Experiments were conducted at three locations representing the precipitation gradient across Kansas in 2022 to characterize hemp growth, nutrient uptake, and soil water depletion. One fiber and one grain variety were evaluated with and without fertilizer nitrogen at Manhattan, Haysville, and Scandia, KS. Both non-irrigated and fully irrigated plots were evaluated at Scandia. Soil water content and biomass accumulation were monitored in plots with full nitrogen fertilizer. Results from the 2022 season confirmed the benefit of nitrogen fertilizer. Although total biomass yield was similar for the two varieties, more of that yield was partitioned to grain in the grain variety and to stalks in the fiber variety. Nutrient uptake patterns were similar to those observed for hemp in previous years and documented in other crops. Nitrogen and potassium accumulation occurred at a faster rate than dry matter, and phosphorus accumulation lagged that of dry matter. Carbon accumulation closely followed total dry matter accumulation. The sum of net depletion of the soil profile water plus precipitation averaged 17.3 inches across the three locations in 2022, but some of the precipitation came in intense events that resulted in runoff. Relatively stable stalk yield coupled with more variable grain yield reveals hemp’s ability to adjust growth to match the inconsistent growing conditions typical of Kansas.
Keywords: biomass; dual-purpose hemp; soil water depletion; hemp water use; biomass hemp; Kansas hemp production; hemp nutrient accumulation